THE NATURE OF EXECUTIVE POWER AND THE ONTOLOGICAL DILEMMA OF POLICE INDEPENDENCE IN THE INDONESIAN CONSTITUTIONAL SYSTEM - Ardin Firanata (NOMOI Law Review, 2026)
This study examines the nature of executive power and the ontological dilemma concerning the independence of the Indonesian National Police (Polri) within the Indonesian constitutional system. Unlike previous studies that generally position Polri merely as a normative component of the executive branch, this research specifically analyzes the tension between Polri’s institutional placement under the President and the demand for independence in carrying out its law enforcement functions. The main issue addressed in this study is the ontological ambiguity regarding the position of Polri, whether it should be understood as a hierarchical executive organ or as a law enforcement institution that must be free from political interference. This research employs a normative juridical method with statutory and conceptual approaches, supported by the analysis of legal doctrines. The analysis focuses on the authority relationship between the President and Polri, the concept of independence in law enforcement, and its implications for the principle of the rule of law (rechtstaat). The findings indicate that constitutionally Polri falls within the scope of executive power, yet functionally it is required to maintain independence in performing its law enforcement duties. This condition creates an ontological dilemma, as Polri is structurally subordinate to the executive branch while simultaneously expected to uphold neutrality and professionalism. This study emphasizes the importance of clearly defining the boundaries between structural subordination and functional independence, in order to prevent undue political interference in law enforcement while ensuring accountability within a democratic system.